Panniculitis in juvenile dermatomyositis: Report of a case and review of the published work - SALMAN, ANDAÇ; ERGUN, SAFİYE ATLAS TÜLİN (WILEY, 2016)
We report a 15-year-old girl who presented with indurated, subcutaneous nodules in addition to classical findings of juvenile dermatomyositis. Histopathological examination confirmed the diagnosis of panniculitis associated with juvenile dermatomyositis. Considering that panniculitis is a rare cutaneous manifestation of juvenile dermatomyositis, we present a patient with a brief review of the published work to highlight the importance of keeping juvenile dermatomyositis in mind among the etiologies of pediatric panniculitis.
Keywords: dermatomyositis; juvenile dermatomyositis; panniculitis; pediatric; subcutaneous tissue; CHILDHOOD DERMATOMYOSITIS; MANIFESTATIONS; SKIN